OTHER DATA PROTECTION PRINCIPLES - Ticher, Paul (Data Protection and the Cloud, 2015)
Although the seventh and eighth data protection principles are those with the greatest relevance to cloud computing, it is worth looking briefly at the other six. This principle, as well as making a general requirement of fairness, specifies that Data Subjects must have ready access to information about who is using their data and what for – the Transparency requirement – and that they must, in some cases, give consent for this. There is also a requirement to indicate who – either in general or specifically – the data may be disclosed to or shared with. Transferring data to a cloud provider does not